SOCIOCULTURAL AND HISTORICAL ASPECTS OF THE PRESERVATION AND DEVELOPMENT OF TRADITIONAL MUSIC OF THE PEOPLES OF CENTRAL ASIA IN THE CONTEXT OF GLOBALISM (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This report examines issues related to solving the problems of preserving and developing the traditional music of the peoples of Central Asia in the context of globalization. The central thesis is the historically determined traditions of living together and the formation of various related genres of traditional music in the region. The cultural aspect of the material under study lies in the fact that for many centuries the peoples of Central Asia have been farming together, often moving from a nomadic lifestyle to a sedentary one, while in many rituals and customs (for example, at the meeting of the spring holiday Navruz) the presence of common elements (including the genre of epic chants) was constantly observed. New socio-economic realities in the context of the formation of independent states are beginning to significantly influence the development of traditional music. Everyone knows that the civilization of the peoples of Central Asia has been created for centuries by the entire community of Iranian and Turki-speaking peoples of the region. However, in the new geopolitical conditions, trends have emerged that strongly hinder the preservation of the regime of cultural interaction. The author suggests implementing a number of actions aimed at ensuring further interaction in the cultural space of the Central Asian region - creating joint textbooks, holding forums, etc.